2018
DOI: 10.1108/ajems-07-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Does FDI moderate the role of public R&D in accelerating agricultural production in Africa?

Abstract: Purpose The agriculture sector in Africa is a major employer, but production levels have fallen short of demand. To match future demand, public investment in research and development (R&D) is required. The purpose of this paper is to investigate how foreign direct investments (FDIs) moderate the effects of public R&D on Africa’s agricultural production. Design/methodology/approach This study estimates an unbalanced panel fixed effect model that consists of 28 African countries covering the period 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Investors are increasingly renting or purchasing the farmland abroad considering the food crisis and limited natural resource in the host country [22]. Adom et al explored how FDI mitigates the impact of public (Research and Development) R&D on agricultural production by using the data of 28 countries in Africa from 1980 to 2014 and the fixed-effect model, and found that FDI has a direct positive impact on agricultural production [23]. Jiang et al discussed the actual impact of China's agricultural FDI and concluded that private enterprises are the pillar of China's agricultural FDI, and agricultural FDI guarantees national food security through expanding the agricultural market, and brings agricultural technology, management experience, and employment opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investors are increasingly renting or purchasing the farmland abroad considering the food crisis and limited natural resource in the host country [22]. Adom et al explored how FDI mitigates the impact of public (Research and Development) R&D on agricultural production by using the data of 28 countries in Africa from 1980 to 2014 and the fixed-effect model, and found that FDI has a direct positive impact on agricultural production [23]. Jiang et al discussed the actual impact of China's agricultural FDI and concluded that private enterprises are the pillar of China's agricultural FDI, and agricultural FDI guarantees national food security through expanding the agricultural market, and brings agricultural technology, management experience, and employment opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the hunger literature, hunger is modelled as a production function-either as a translog production function or a Cobb-Douglas production function. This is due to its correlation with food production [ 32 , 55 , 56 ]. Following the dynamic model proposed by [ 38 ], that modelled hunger of country (i) at a specific time (t) as an unobserved latent variable (y it ); in this study, variable (y it ) represents women-hunger in each country for a particular year.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Adom et al (2018) study the impacts of public R&D on Africa's agricultural productivity on FDI. This study uses an imbalanced panel fixed effect model to estimate data for 28 African nations from 1980 to 2014.…”
Section: Literature Reviewmentioning
confidence: 99%